Sacred matters : religion and spirituality in families - Burr, Wesley R., 1936-; Marks, Loren Dean.; Day, Randal D., 1948- (New York : Routledge Academic, 2011)
'Sacred Matters builds on earlier literature, adds new qualitative and quantitative data, and creates a conceptual framework and general theory (or model) about when, how, and why sacred matters are helpful and harmful in families'--
Includes bibliographical references and index.
Keywords: Families -- Religious life; Spiritual life; Families -- Research; FAMILY & RELATIONSHIPS / Family Relationships; PSYCHOLOGY / Interpersonal Relations; RELIGION / Psychology of Religion